Alcohol in Daily Products: Health Risks, Cultural Considerations, and Economic Impacts - Herdiana Y (Risk Management and Healthcare Policy)
Yedi Herdiana Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, IndonesiaCorrespondence: Yedi Herdiana, Email y.herdiana@unpad.ac.idAbstract: Ethanol, a bioactive compound prevalent in both social and industrial applications, is present in alcoholic beverages as well as a range of everyday products. In food, ethanol functions primarily as an additive or a by-product of fermentation, while in pharmaceuticals and cosmetics, it serves as a solvent or preservative. Despite its widespread use, three critical research gaps exist in current literature. First, existing research focuses predominantly on single-sector analyses, overlooking the cumulative effects of cross-sectoral ethanol exposure. Second, despite growing global market integration, there is limited understanding of how cultural and religious requirements influence ethanol-related regulations and product formulations. Third, current economic models fail to integrate both health impact costs and cultural compliance expenses, hindering effective policy development. The World Health Organization has determined that no amount of alcohol consumption can be considered entirely safe, as ethanol’s health impacts include contributions to chronic diseases, neurotoxicity, and potential carcinogenic effects. These risks are compounded by the pervasive and often unrecognized presence of ethanol in various products, particularly affecting vulnerable populations. The economic burden associated with alcohol-related issues, including lost productivity and healthcare costs, highlights the necessity for robust public health strategies and stringent regulatory guidelines. This review investigates ethanol’s role across multiple domains, emphasizing its presence in food, medicine, cosmetics, and industrial products, and evaluates its broader implications for public health, cultural practices, and economic impact. This review recommend implementing standardized labeling systems, establishing cultural-sensitive alternatives in product formulations, and developing harmonized international guidelines for ethanol use across industries.Keywords: ethanol safety standards, public health risk management, acetaldehyde, stress oxidative, cultural-sensitive product